Real-Time In Vivo Monitoring of Cholinergic Neurotransmission in the Mouse Brain Using a Microelectrochemical Choline Biosensor - Cunningham, Colm (My University, 2025)
The measurement of choline as a biomarker for in vivo cholinergic neurotransmission is a valuable tool in the study of a range of CNS pathologies. However, the continuous detection of cholinergic neurotransmission in selective brain regions in the mouse brain remains challenging and underexploited. Here, we have refined an established choline oxidase (ChOx) microelectrochemical biosensor and validated its use for long-term recording in the freely moving mouse. Using a 75-μm diameter polymer- ChOx composite disc electrode, we have successfully monitored stable and reproducible chronic real-time changes in choline-induced amperometric currents in vivo. Local infusions of choline and acetylcholine resulted in an increase in biosensor current in the hippocampus, while the inhibition of endogenous acetylcholinesterase (with neostigmine) significantly attenuated the response to exogenous acetylcholine. Systemic administration of donepezil produced a pronounced decrease in current in both the prefrontal cortex and hippocampus, with scopolamine and amphetamine resulting in signal increases that were not observed in animals with selective saporin lesioning (murine-p75) of the cholinergic basal forebrain. Furthermore, continuous biosensor recording in both regions displayed diurnal oscillations across repetitive light–dark phases. All are consistent with successful monitoring of endogenous changes in cholinergic neurotransmission.
PUBLISHED
Keywords: Ageing; Immunology, Inflammation & Infection; Neuroscience